OPTIMISING BALANCE AND GAIT IN STROKE PATIENTS: A COMPARATIVE STUDY OF SWISS-BALL DUAL-TASK EXERCISES VS. CONVENTIONAL THERAPY - Dey, Arghya Prakash; Jain, Annu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Stroke is a leading cause of long-term disability worldwide, with balance and gait impairments being common sequelae. This study aimed to compare the effectiveness of Swiss-Ball dual-task exercises versus conventional therapy in improving balance and gait parameters in post-stroke patients. In this randomized controlled trial, 64 stroke survivors (aged 25-65 years) were allocated to either a Swiss-Ball dual-task exercise program (n=32) or conventional therapy (n=32) for 8 weeks. Outcome measures included the Berg Balance Scale (BBS), Timed Up and Go Test (TUG), 10-Meter Walk Test (10MWT), and Functional Gait Assessment (FGA). Results demonstrated that patients in the Swiss-Ball dual-task group showed significantly greater improvements in dynamic balance (mean BBS improvement 8.7±2.3 vs. 5.4±2.1, p<0.001) and functional mobility (mean TUG improvement 4.2±1.1 vs. 2.8±1.3 seconds, p<0.01) compared to the conventional therapy group. Both interventions improved gait speed, but the Swiss-Ball group demonstrated superior outcomes in dual-task gait parameters. These findings suggest that Swiss-Ball dual-task exercises may provide enhanced rehabilitation outcomes for balance and gait recovery in stroke patients compared to conventional approaches. Incorporating this innovative intervention could optimize functional recovery and potentially reduce fall risk in the stroke population.